Determinants of Consumption Values and Their Impact on Green Purchase Intention through Green Trust: Case Study on the Purchase and Use of Xiaomi Electric Scooter Products in Jabodetabek - Deyna Dwitama Setiadi; Hari Muharam; Sufrin Hannan (PT. Publikasiku Academic Solution, 2024)
This study aims to analyze the determinants of consumption value and their impact on green purchase intention through green trust in a case study on the purchase and use of Xiaomi electric scooter products in Jabodetabek. This study used quantitative accidental sampling method by conducting survey techniques using questionnaire instruments. The questionnaire was distributed to 150 respondents in the Jabodetabek area and the classification of respondents were those who had known, had used, and had bought electric scooter products. The analysis techniques used are descriptive statistics and Structural Equation Modeling (SEM). The results of this study state that consumption values consisting of functional value, social value, and emotional value have a significant influence on green trust both individually and together, consumption values have a significant influence on green purchase intention, green trust has a significant influence on Green Purchase Intention, as well as Consumption Values and Green Trust together have a significant influence on Green Purchase Intention.